1988
DOI: 10.1111/j.1365-2125.1988.tb05303.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of sibutramine hydrochloride (BTS 54524), a new antidepressant, in healthy volunteers.

Abstract: The cardiovascular, anticholinergic and central effects of single doses of 30, 45 and 60 mg of sibutramine hydrochloride (BTS 54524), a new potential antidepressant, were compared with amitriptyline (50 mg) and placebo given at weekly intervals in a randomised design to six healthy male volunteers. Sibutramine was associated with increases in both supine heart rate and systolic blood pressure at 1, 2 and 6 h after 60 mg (P < 0.05). Amitriptyline caused a significant 50-60% decrease in salivation compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 10 publications
2
15
0
3
Order By: Relevance
“…33 Our results show, however, that 10 mg and 15 mg sibutramine treatments were associated with a signi®cant increase in heart rate, compared with the placebo. Such observations have previously been reported by King and Devaney 13 in healthy volunteers with a single dose of 45 mg or 60 mg sibutramine. Cole et al 14 also reported changes in heart rate following once-daily doses of 20 mg or 30 mg sibutramine.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…33 Our results show, however, that 10 mg and 15 mg sibutramine treatments were associated with a signi®cant increase in heart rate, compared with the placebo. Such observations have previously been reported by King and Devaney 13 in healthy volunteers with a single dose of 45 mg or 60 mg sibutramine. Cole et al 14 also reported changes in heart rate following once-daily doses of 20 mg or 30 mg sibutramine.…”
Section: Discussionsupporting
confidence: 70%
“…9±12 In healthy volunteers, sibutramine appears to be free from anticholinergic effects. 13 It has no amphetamine-like abuse potential in either animals 8 or recreational drug users. 14 In rats, sibutramine causes a dose-dependent decrease in food intake and bodyweight.…”
Section: Introductionmentioning
confidence: 99%
“…In human, the acute administration of a single dose of sibutramine elevated systolic blood pressure and heart rate (HR) for at least 6 h (King and Devaney, 1988). Furthermore, chronic treatment of obese patients with sibutramine (20 mg day Ϫ1 for 6 months), caused modest, but significant, increases in mean arterial blood pressure (MAP) (2-3 mm Hg) and HR (3)(4)(5) beats min Ϫ1 ) (Fujioka et al, 2000).…”
mentioning
confidence: 99%
“…No entanto, estudos clínicos não evidenciaram eficácia antidepressiva. [15][16][17] De forma diferente, não existe evidência de redução dos sintomas relacionados ao TOC com o uso dessas substâncias.…”
Section: Russelunclassified